A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages After general training there are various opportunities open to the nurse according to her individual leanings. She may continue with hospital work as a staff nurse, rising through the rank of sister to more responsible posts. To many with a gift for teaching a special course for a sister-tutorship will be an attraction. On the non-institutional side such posts as health visitors, tuberculosis visitors, school nurses, dental nurses, midwives, etc., all involving some specialised additional training, offer attractive vocations. The accompanying Chart (see Appendix) shows the various posts in progressive form with necessary qualifications and the possibilities of interchangeability advocated and encouraged by N.A.L.G.O. It remains for the authorities themselves to afford the necessary facilities. A Brief Survey of Present Difficulties There is no unemployment in the nursing profession — indeed, the position at present is very much the reverse. A shortage of trained staff is causing serious embarrassment and a solution to the problem must be found without delay. It is not within the scope of this brochure to dilate at length on the existing system of recruitment and training. An exhaustive review will be found in the Final Report of the Lancet Commission on Nursing (1932), published by The Lancet, Limited, price 2s. 6d. net. Reference might also be made to the “Choice of Career” Series, No. 17 (Stationery Office, price 4d.). Under present conditions, with the nursing of the sick in the hands of two main groups (local authorities and voluntary organizations), one factor of paramount importance emerges from a study of the Lancet Report — the immediate need of standardization in this section of the public service. Five years have elapsed since the issue of the Report, and no serious attempt appears to have been made in this direction by any of the national bodies whose primary responsibility it should be to ensure the recruitment and training of an adequate and contented personnel. As regards the public service generally, it has been the officers’ organization — the National Association of Local Government Officers — which has always taken the lead in the formulation of schemes for the recruitment and vocational training of staff and to ensure better service conditions. 4 292/54.73/2/1